Mechanical behavior and characterization of Al7075 reinforced with Al2O3 and TiC Hybrid metal matrix composite. (2022) - Radha, A.; Antony Prabu, D.; Jayakumar, KS.; Sankaralingam, T.; Selvam, B.; Balaharsha, S.
Abstract: The fabrication and analysis of Aluminium 7075 Metal Matrix composite is designed to set up the use of a substitute metal for aerospace applications. Aviation and car businesses are enthusiastic on presenting mixture metal grid composites in their segments because of their excellent mechanical and wear properties, prompting decrease in the weight underlying segments and energy prerequisite for driving. This research paper includes investigation of the mechanical properties of the Al7075 reinforced with 6 wt% of Aluminium Oxide and various weight percent (wt%) of Titanium Carbide (TiC) in micron level particles manufactured by stir casting technique. The examination of mechanical properties like hardness, tensile strength, impact strength (Charpy) was investigated. The microstructure concentrated by scanning electron microscope instruments is done to notice the kind of fortified particles conveyance in composite. Results from wear test showed that the wear rates of the pin on disc Al7075 alloy and composites increasing with applied load. The mechanical properties of the created composites are looked at and reasonable suggestions will be proposed. We additionally confronted imperatives to acquire the parts consistent with the ASTM testing norms.